Nutritional Management in Pregnant Patient with Severe Preeclampsia: A Case Study - Nur Sakinah; Zulfiani Zulfiani; Abdullah Tamrin (Jurnal EduHealth, 2026)
Preeclampsia is a serious pregnancy complication and a leading cause of maternal mortality, often contributing to preterm birth and low birth weight. This condition increases the risk of edema and nutritional deficiencies, which negatively impact both maternal and fetal health. This descriptive case study aims to evaluate the effectiveness of the Nutrition Care Process (NCP) in improving nutrient intake and clinical outcomes in a pregnant patient with severe preeclampsia. The methodology follows a standardized five step nutrition care process, including screening, assessment, diagnosis, intervention, monitoring and evaluation, with nutritional requirements calculated based on ESPEN (2021) guidelines. Interventions included the DASH and preeclampsia diets with an oral soft consistency, administered gradually from 50% to 100% of energy needs. Monitoring results demonstrated a significant increase in daily intake: energy (47.7% to 95%), protein (54.3% to 123%), fat (50.6% to 110%), and carbohydrates (40.3% to 85.8%). These improvements were accompanied by better food tolerance, reduced edema, and stabilized blood pressure. In conclusion, the structured application of NCP is effective in enhancing nutrient intake and supporting the clinical management of patients with severe preeclampsia. These findings highlight the importance of standardized nutrition therapy as a critical component in reducing the risk of complications in high risk pregnancies.